Kajian Strategi Pemasaran Ubi Cilembu (Kasus di Desa Cilembu, Kecamatan Pamulihan, Kabupaten Sumedang) - Ervina, Cordelia; Hubeis, Musa; Pandjaitan, Nora H. (Institut Pertanian Bogor, 2019)
One of areas which producing sweet potato is Cilembu Village, located in Pamulihan Subdistrict, Sumedang Regency. The sweet Potato is famous as ubi Cilembu. The objectives of this research were to identify internal and external factors affecting raw material availability and continuity of marketing system of sweet potato Cilembu and to recommend alternative of effective and efficient marketing strategy of sweet potato Cilembu. This research used purposive sampling and also primary and secondary data. Respondents consisted of 30 people from 107 population of sweet potatoes Cilembu in Cilembu village. Analysis was conducted using IFE and EFE matrix, internal-external (IE) matrix, SWOT and QSPM method. From several strategies by using QSPM method, it had chosen one strategy to boost Cilembu sweet potato marketing by KUCP. The strategy was to encourage efforts in creating processing business medium scale of Cilembu sweet potatoes in order to get competitive processed products.